2023
DOI: 10.5093/pi2023a2
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of a Child-centred Psychosocial Healthcare Intervention (KIDPROTEKT) – Results of a Cluster Randomized Controlled Trial in Paediatric and Gynaecologic Practices

Abstract: Evaluation of a child-centred psychosocial healthcare intervention (KID-PROTEKT) -Results of a cluster randomized controlled trial in paediatric and gynaecologic practices.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 45 publications
(54 reference statements)
0
2
0
Order By: Relevance
“…We found that around a quarter of participants in both groups utilized the recommended services. This approximately corresponds to the percentage of the whole sample in the main study [35]. A German study found that 30% of mentally ill parents engaged in psychotherapy and 12% in family services [22], whereas a US representative study revealed a utilization rate of 40% in the general population [23].…”
Section: Discussionmentioning
confidence: 84%
See 1 more Smart Citation
“…We found that around a quarter of participants in both groups utilized the recommended services. This approximately corresponds to the percentage of the whole sample in the main study [35]. A German study found that 30% of mentally ill parents engaged in psychotherapy and 12% in family services [22], whereas a US representative study revealed a utilization rate of 40% in the general population [23].…”
Section: Discussionmentioning
confidence: 84%
“…This sub-study was part of a multicenter, randomized controlled trial on the effectiveness of KID-PROTEKT conducted in 24 gynecologic (n = 13) and pediatric (n = 11) medical practices in Hamburg, Germany, and surrounding rural areas. The results of the main trial are reported in a separate paper [35]. The present paper comprises findings on secondary outcomes in a sub-sample of the main trial.…”
Section: Methodsmentioning
confidence: 99%